The Therapeutic Intervention of Sex Steroid Hormones for Sarcopenia - Huang, Le-Tian; Wang, Jia-He (Frontiers in Medicine, 2021)
Sarcopenia, characterized by the excessive loss of skeletal muscle mass, strength, and function, is associated with the overall poor muscle performance status of the elderly, and occurs more frequently in those with chronic diseases. The causes of sarcopenia are multifactorial due to the inherent relationship between muscles and molecular mechanisms, such as mitochondrial function, inflammatory pathways, and circulating hormones. Age-related changes in sex steroid hormone concentrations, including testosterone, estrogen, progesterone, and their precursors and derivatives, are an important aspect of the pathogenesis of sarcopenia. In this review, we provide an understanding of the treatment of sarcopenia through the regulation of sex steroid hormones. The potential benefits and future research emphasis of each sex steroid hormone therapeutic intervention (testosterone, SARMs, estrogen, SERMs, DHEA, and progesterone) for sarcopenia are discussed. Enhanced understanding of the role of sex steroid hormones in the treatment for sarcopenia could lead to the development of hormone therapeutic approaches in combination with specific exercise and nutrition regimens.